Synthesis of Magnetic Catalyst Derived from Oil Palm Empty Fruit Bunch for Esterification of Oleic Acid: An Optimization Study - Shamala Gowri Krishnan; Fei-Ling Pua; Ee-Sann Tan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
Biomass, renewable, abundantly available and a good source of energy. The conversion of biomass waste into valuable products has received wide attention. In this study, an empty fruit bunch (oil palm EFB) supported magnetic acid catalyst for esterification reaction was successfully prepared via the one-step impregnation process. The new magnetic catalyst achieved a higher surface area of 188.87 m2/g with a total acidity of 2.4 mmol/g and identified iron oxide as g-Fe2O3. The magnetization value of 24.97 emu/g demonstrated that the superparamagnetic catalyst could be easily recovered and separated after the reaction using an external magnet. The catalytic performance of oil palm EFB supported magnetic acid catalyst was examined by esterification of oleic acid. Esterification process parameters were optimized via Response Surface Methodology (RSM) optimization tool with Box-Behnken design (BBD). The following optimum parameters were determined: an amount of 9 wt% catalyst, molar ratio of methanol to oleic acid of 12:1, reaction time of 2 h and reaction temperature of 60 °C with a maximum conversion of 94.91% was achieved. The catalyst can be recycled up to five cycles with minimal loss in its activity. The oil palm waste-based magnetic acid catalyst indicates its potential replacement to the existing solid catalysts that are economical and environmentally friendly for the esterification process in biofuel applications. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).